Atrial fibrillation in patients with hypertrophic cardiomyopathy as a risk factor for additional cardiovascular complications - K. Rudenko; L. Nevmerzhytska; S. Fanta; O. Dudnyk (Ukrainian Journal of Cardiovascular Surgery, 2018)
The article presents a review of literature data and the experience of treating patients with hypertrophic cardiomyopathy (HCM) and atrial fibrillation. Patients with HCM have a high level of prevalence of atrial fibrillation, which is associated with a significant increase in the risk of stroke and heart failure. According to various researches, the prevalence of AF is described as 12–28% in patients with HCM. Therefore, it is important to determine the predictors of development of AF at HCM. Atrial fibrillation in patients with HCM is a multifactorial disease. In numerous studies it has been shown that the predictors include: obstruction of the left ventricular outflow tract, increased size of the left atrium >50 mm, involvement of the right heart, age >60 years, increased level of the NT-proBNP, specific gene mutations. Patients with HCM with one or more risk factors for AF should be thoroughly examined with Holter monitoring in the dynamics. We analyzed the data about patients with HCM who were treated at the Amosov National Institute of Cardiovascular Surgery from 2009 to 2018. Patients were divided into two groups: the first group of patients who were treated by alcoholic septal ablation and the second group of patients who were treated by Ferrazzi procedure. The mean systolic pressure gradient in the left ventricular outflow tract, the presence of AF before surgery and in the short-term period after endovascular and surgical treatment, and the presence of thromboembolic complications were evaluated. The analysis of the short-term results after invasive methods of treatment of HCM (alcohol septal ablation and Ferrazzi procedure) showed that a decrease of the mean systolic pressure gradient in the left ventricular outflow tract is associated with a significant decrease in the probability of AF appearence.